-14+6.5x=-24x+5.7

Simple and best practice solution for -14+6.5x=-24x+5.7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -14+6.5x=-24x+5.7 equation:



-14+6.5x=-24x+5.7
We move all terms to the left:
-14+6.5x-(-24x+5.7)=0
We get rid of parentheses
6.5x+24x-5.7-14=0
We add all the numbers together, and all the variables
30.5x-19.7=0
We move all terms containing x to the left, all other terms to the right
30.5x=19.7
x=19.7/30.5
x=11.5882352941/17.9411764706

See similar equations:

| 6x+3=4+5 | | (1/5)/(3/13)=x | | 0=-5x^2+9x=126 | | 3(x-6)2=5x-4 | | 7-4d(1d-3)=23 | | 25-10x=8 | | -14+6.5x=-37+5x | | x/(3/13)=1 | | 4x-5(3-3x)=x-7(4-x)-9 | | 3(7-x)-(x+2)=5+7(x-9) | | 3n-1=1/8 | | 21x/4-4/3=76 | | 5k−2=7 | | 2/3x+5/7=11/5(x+2) | | 5(z+6)=4(z-8)+z | | 27x+5=23.4x-1 | | 75+20x=35 | | 3x–1=6+2x | | 3m^2-2m+12=0 | | 24x-48÷6=4 | | 5x=11(2x-3)÷2 | | p+3=7-9p | | 12x2+24=0 | | 3x+1=11=2x | | 1/3(9x-12)-6x+15=-19 | | 95x=35x | | 5x=11(2x-3÷2) | | 7(5x-4)=3(8-5x) | | 8m-4=3+8 | | 5x-14+3x+2+x+32=180 | | 8w-8=4w-7 | | 90+5.45x=13.63x |

Equations solver categories